Accelerations from wearable accelerometers reflect knee loading during running after anterior cruciate ligament reconstruction - Havens, K. L.; Cohen, S. C.; Pratt, K. A.; Sigward, S. M. (Clinical Biomechanics, 2018)
Following anterior cruciate ligament reconstruction, individuals exhibit sagittal plane knee loading deficits as they underload their injured limb during running. These between-limb biomechanical differences are difficult to clinically detect. Wearable accelerometers may aid in the development of early rehabilitation programs to improve symmetrical loading. This study aimed to identify whether segment accelerations from wearable accelerometers can predict knee loading asymmetry in an anterior cruciate ligament reconstructed population. Methods: 14 individuals 5-months post-anterior cruciate ligament reconstruction performed self-selected speed running. Data were collected concurrently using a marker-based motion system and accelerometers positioned on participants' shanks and thighs. Stepwise linear regression was used to determine predictive value of accelerometer data on biomechanical variables. Finding: Shank acceleration was not predictive of any biomechanical variable. Between-limb differences in thigh axial acceleration explained 30% of the variance in between-limb differences in knee power absorption (p = 0.045), suggesting that accelerometers placed on proximal joint segments may provide information regarding knee loading asymmetry. Between-limb differences in thigh axial acceleration also explained 38% of the variance in between-limb differences in ground reaction force (p = 0.002). Interpretation: These relationships indicate that accelerations from wearable accelerometers may provide some useful information regarding knee loading during running in individuals following anterior cruciate ligament reconstruction.